Undernutrition and associated factors among pregnant women in East Borena Zone, Liban District, Oromia regional state, Ethiopia - Arero, Godana (Frontiers in Nutrition, 2022)
Background: Undernutrition is “cellular imbalance b/n supply of nutrients, energy and body’s demand to ensure growth, maintenance, and specific function. However, there was no study conducted earlier on this topic in East Borena Zone. Objective: To assess the prevalence of undernutrition and associated factors among pregnant women in East Borena Zone, Liban district. Method: A community-based cross-sectional study was conducted on 500 study participants from November 20 to December 2021. The systematic sampling technique and simple random sampling methods were used to select study participants. Data were double entered into Epi-info software version 7 and SPSS version 21 software for analysis. Descriptive statistics were used to describe the characteristics of study participants. Bivariate and multivariable logistic regressions were carried out to identify the association between independent and dependent variables measuring the adjusted odds ratio and 95% confidence interval. P-values less than 0.05 were considered statistically significant. Results: Prevalence of undernutrition among pregnant women was about (44.9%) family monthly income [AOR=8.72 (4.80, 15.83)], women decision making autonomy [AOR=0.40 (0.19, 0.82)], skipping meal [AOR=2.62 (1.41, 4.89)], substance use [AOR=2.01 (1.07, 3.77)], household food insecurity [AOR=2.01 (1.06, 3.80)], lack of prenatal dietary advices [AOR=2.73 (1.53, 4.89)], absence of household latrine [AOR=9.23 (3.48, 24.46)], not participating health development army’s meeting at village level [AOR=3.01 (1.57, 5.72)] and hand washing habit [AOR=6.55 (3.02, 14.20)] had shown statistically significant association with undernutrition. Conclusion: The prevalence of undernutrition among pregnant women was high income, women's decision making autonomy, skipping meals, substances use, household food insecurity, lack of prenatal dietary advice, poor hand washing habit, lack of latrine, and not a participation in health development army’s meeting were found to be predictors of the undernutrition.